COMMUNITIES AT RISK: AN AFTERMATH OF GLOBAL CAPITALISM - Adalikwu-Obisike, Justina; Obisike, Ebere E. (European Scientific Journal, ESJ, 2014)
The purpose of this paper was to highlight community risks that are a product of global capitalism, as perpetuated through the activities of Oil Multinational Corporations (MNCs) in the Niger Delta Region of Nigeria. Like globalization, global capitalism characterizes the paradoxical coexistence of free market enterprise and community risks. The progress in the use of modern technologies no doubt exposes our societies to several socio-economic and health risks. These risks are more prevalent in oil producing communities, where the desire to amass wealth at all costs is the major factor propelling the socio-economic activities by the governments and the oil MNCs. This paper is based on our field study, which commenced in 2004 and culminated in 2013, in five communities in the Niger Delta region of Nigeria. However, the analysis of the core issues in this paper was influenced by Beck’s concept of the Risk Society. The position of this paper is that although the exploration of crude oil in the Niger Delta has brought some socio-economic gains to a few connected to the Nigerian government, majority of the people, particularly those in the oil producing region are faced with a plethora of risks in their daily lives.